2018
DOI: 10.1051/matecconf/201814402007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of precipitation hardened Al7075-grey cast iron powder reinforced metal matrix composites

Abstract: Abstract. Al7075 alloy is the most commonly used by the aerospace industry. Al7075 alloy is characterized by its improved properties such as higher toughness, specific strength and hardness. The current work focuses on the preparation and characterization of age hardened Al7075-Grey cast iron composites. Two stage stir casting technique is used for the preparation of the composite. Age hardening treatment is imparted to enhance the mechanical characteristics. The variation of hardness and tensile strength with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Specimens were prepared as per the international standards and tensile, hardness and impact tests are performed.It was found that hardness increases with increase in wt% of SiC reinforcement. Hardness and tensile strength of 6wt% SiC composite is found to be higher than 2 & 4 wt% of SiC [3]. The tensile and fracture behaviour of as cast and age hardened aluminum (6063), silicon carbide particulate composites produced, using borax additive and a twostep stir casting method.…”
Section: Introductionmentioning
confidence: 98%
“…Specimens were prepared as per the international standards and tensile, hardness and impact tests are performed.It was found that hardness increases with increase in wt% of SiC reinforcement. Hardness and tensile strength of 6wt% SiC composite is found to be higher than 2 & 4 wt% of SiC [3]. The tensile and fracture behaviour of as cast and age hardened aluminum (6063), silicon carbide particulate composites produced, using borax additive and a twostep stir casting method.…”
Section: Introductionmentioning
confidence: 98%